Seasonal chlorophyll variations in Tabebuia avellanedae and Anadenanthera colubrine leaves - Freiberger, Mariângela Brito [UNESP]; Castoldi, Gustavo [UNESP]; Marini, Deniele; Lang, Aleteia; Herzog, Neusa Francisca Michelon; Malavasi, Ubirajara Contro (Universidade Estadual de Londrina, 2010)
The experiment had the aim of quantifying seasonal chlorophyll variation on leaves of Anadenanthera colubrina and Tabebuia avellanedae. The experiment used a randomized block design established as a 2 x 3 factorial (two species and three sampling seasons) with 5 replications. The concentrations of chlorophyll in leaves were performed at the end of winter, late spring, and summer. The content of chlorophyll a changed only for A. colubrina, bringing up from spring (117.52 ?g mL-1) to summer (151.13 ?g mL-1). For the two species, the proportion of chlorophyll b was higher between periods at the end of spring (average of 29.31 μg mL-1) to the end of summer (average of 74.96 ?g mL-1) with close relationship with the decrease in global solar irradiance. The chlorophyll a/b relationship increased in late spring due to reduction of chlorophyll b content. A. colubrina showed greater adaptation to the studied environment.
Varia̧ão sazonal de clorofilas em folhas de Tabebuia avellanedae e Anadenanthera colubrine
Keywords: Acclimation; Heliophytic species; Luminosity